Rhyming slang as a means of masking alcohol and drug addictions - E. Y. Gorshunova; Y. V. Gorshunov (Vestnik MGIMO-Universiteta)
The article is concerned with analysis of rhyming slang euphemisms for some addictions (alcoholism and drug–taking). In the focus of attention is the concept “intoxicated/drug intoxicated”, the means of its representation and euphemistic rhyming slang names of some drugs and doses.